NL ARMS Netherlands Annual Review of Military Studies 2020 Deterrence in the 21st Century Insights from Theory and Practice - Osinga, Frans; Sweijs, Tim.; SpringerLink (Online service) (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2021)
This open access volume surveys the state of the field to examine whether a fifth wave of deterrence theory is emerging. Bringing together insights from world-leading experts from three continents, the volume identifies the most pressing strategic challenges, frames theoretical concepts, and describes new strategies. The use and utility of deterrence in today s strategic environment is a topic of paramount concern to scholars, strategists and policymakers. Ours is a period of considerable strategic turbulence, which in recent years has featured a renewed emphasis on nuclear weapons used in defence postures across different theatres; a dramatic growth in the scale of military cyber capabilities and the frequency with which these are used; and rapid technological progress including the proliferation of long-range strike and unmanned systems. These military-strategic developments occur in a polarized international system, where cooperation betweenleading powers on arms control regimes is breaking down, states widely make use of hybrid conflict strategies, and the number of internationalized intrastate proxy conflicts has quintupled over the past two decades. Contemporary conflict actors exploit a wider gamut of coercive instruments, which they apply across a wider range of domains. The prevalence of multi-domain coercion across but also beyond traditional dimensions of armed conflict raises an important question: what does effective deterrence look like in the 21st century? Answering that question requires a re-appraisal of key theoretical concepts and dominant strategies of Western and non-Western actors in order to assess how they hold up in today s world. Air Commodore Professor Dr. Frans Osinga is the Chair of the War Studies Department of the Netherlands Defence Academy and the Special Chair in War Studies at the University Leiden. Dr. Tim Sweijs is the Director of Research at The Hague Centre for Strategic Studies and a Research Fellow at the Faculty of Military Sciences of the Netherlands Defence Academy in Breda.
Chapter 1. Introduction -- Part I. Concepts of Deterrence (Evolution, Rediscovery, Conventional, Nuclear, Cross-domain) -- Chapter 2. Understanding Deterrence -- Chapter 3. Deterrence Rediscovered: NATO and Russia -- Chapter 4. The Continuing Relevance of Conventional Deterrence -- Chapter 5. Nuclear Deterrence: A Guarantee for or Threat to Strategic Stability? -- Chapter 6. The US and Extended Deterrence -- Chapter 7. Deterrence by Punishment or Denial: The EFP Case -- Chapter 8. The Essence of Cross-domain Deterrence -- Part II. Non-Western Concepts of Deterrence -- Chapter 9. Deterrence à la Ruse: Its Uniqueness, Sources and Implications -- Chapter 10. An Overview of Chinese Thinking about Characteristics of Deterrence -- Chapter 11. Japanese Concepts of Deterrence -- Chapter 12. Deterrence (In)stability between India and Pakistan -- Chapter 13. Iran s Syria Strategy -- Chapter 14. The Evolution of Deterrence -- Part III. Deterrence of Non-State Actors -- Chapter 15. Deterring Violent Non-State Actors -- Chapter 16. All Deterrence is Local: The Utility and Application of Localised Deterrence in Counterinsurgency -- Chapter 17. This has triggered a civil war: Russian Deterrence of Democratic Revolts -- Chapter 18. Deterrence in Peace Operations -- Part IV -- New Instruments and Domains of Deterrence -- Chapter 19. Sanctions and Deterrence: Targeted Sanctions -- Chapter 20. Deterrence, Resilience and the Shooting Down of Flight MH17 -- Chapter 21. Cyber Deterrence: The Past, Present, and Future -- Chapter 22. New Technologies and Deterrence: Artificial Intelligence and Adversarial Behaviour -- Part V Rationality, Psychology and Emotions -- Chapter 23. Nuclear Deterrence in the Algorithmic Age: Game Theory Revisited -- Chapter 24. What s on the Human Mind? Decision Theory and Deterrence -- Chapter 25. Deterrence: A Continuation of Emotional Life with the Admixture of Violent Means -- Chapter 26. The Missing Component in Deterrence Theory: The Legal Framework -- Conclusion: Insights fromTheory and Practice.
Accessibility summary: This PDF eBook is produced by a third-party. We have requested that the file be made accessible and compliant with the European Accessibility Act (EAA). However, we have not been able to fully verify its compliance with recognized accessibility standards (such as PDF/UA or WCAG). For detailed accessibility information, please refer to the original publisher s website. If you require an accessible version of this content, please contact accessibilitysupport@springernature.com. We are committed to improving accessibility and will work with the publisher to meet your needs wherever possible.
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International law; Security, International; Political science; Public International Law; International Security Studies; Politics and International Studies